PENGARUH PEMBERIAN MADU UNTUK PENCEGAHAN JERAWAT - Junaidah, Rini (JIMR : Journal Of International Multidisciplinary Research, 2024)
Honey is a type of food with a high sugar content and low fat that has a sweet and thick taste that is golden to dark brown in color. Olive oil, a type of vegetable oil that contains the highest nutrients in the form of vitamins and minerals, and is low in cholesterol and fat, is able to prevent the body from excess fat which can cause a number of diseases, such as arteiosclerosis (thickening of the walls of the arteries), high blood pressure (hypertension). , chest pain, improves breathing, prevents stomach ulcers, helps the process of digestion of food, hepatitis, kidney stones, diabetes, respiratory disorders, disorders. In beauty treatments, vitamin E is used after exfoliating dead skin to stimulate the formation of new skin tissue. Using vitamin E externally soothes inflammation and removes scars. Vitamin E especially helps treat acne contained in olive oil. Natural honey is a product produced by bees from nectar and sweet deposits found in various parts of plants and trees. This honey is collected and made from nectar or sweet juice found in various parts of plants and trees. This honey has biological and caloric value (contains sugar, vitamins and enzymes), and has many uses depending on the type.